Love & leftovers : a novel in verse - Tregay, Sarah (Katherine Tegen Books, 2012)
When her father starts dating a man, fifteen-year-old Marcie's depressed mother takes her to New Hampshire but just as Marcie starts falling for a great guy her father brings her back to Idaho, where all of her relationships have become strained.